Mechanical Ventilation Lessons Learned From Alveolar Micromechanics - Kollisch-Singule, Michaela; Satalin, Joshua; Blair, Sarah J.; Andrews, Penny L.; Gatto, Louis A.; Nieman, Gary F.; Habashi, Nader M. (Frontiers in Physiology, 2020)
Morbidity and mortality associated with lung injury remains disappointingly unchanged over the last two decades, in part due to the current reliance on lung macro-parameters set on the ventilator instead of considering the micro-environment and the response of the alveoli and alveolar ducts to ventilator adjustments. The response of alveoli and alveolar ducts to mechanical ventilation modes cannot be predicted with current bedside methods of assessment including lung compliance, oxygenation, and pressure-volume curves. Alveolar tidal volumes (Vt) are less determined by the Vt set on the mechanical ventilator and more dependent on the number of recruited alveoli available to accommodate that Vt and their heterogeneous mechanical properties, such that high lung Vt can lead to a low alveolar Vt and low Vt can lead to high alveolar Vt. The degree of alveolar heterogeneity that exists cannot be predicted based on lung calculations that average the individual alveolar Vt and compliance. Finally, the importance of time in promoting alveolar stability, specifically the inspiratory and expiratory times set on the ventilator, are currently under-appreciated. In order to improve outcomes related to lung injury, the respiratory physiology of the individual patient, specifically at the level of the alveolus, must be targeted. With experimental data, this review highlights some of the known mechanical ventilation adjustments that are helpful or harmful at the level of the alveolus.